Faktor-Faktor Risiko Kawin Berulang pada Sapi Potong di Kecamatan Licin, Kabupaten Banyuwangi, Jawa Timur - Damayanti, Putri Nurmalia; Sardjito, Trilas; Prastiya, Ragil Angga (Jurnal Veteriner; Vol 21 No 4 (2020)DO - 10.19087/jveteriner.2020.21.4.550, 2020)
Nowadays, beef cattle farms in Licin Subdistrict, Banyuwangi Regency have problems in providing beef demand because the less of productivity. This problems occured due to the repeat breeding case and decrease the efficiency and productivity of livestock. It suspected because of the lack of hygine and sanitation from farmers and inseminator. This study aimed to correlate the factors and cases of repeat breeding on beef cattle in Licin Subdistrict, Banyuwangi Regency. It was a descriptive study which used 69 cow with simple random sampling method. Primary data was obtained from direct observation of livestock, then continued with interviewing farmers using in-depth study system. While secondary data is obtained from the records of inseminator. It included the term of farming, farmer’s ability to detect estrus cycle, housing and the feeding of beef cattle. The collected data was analyzed by descriptive statistic, then processed by using SPSS 22.0. Chi Square Test (X 2 ) was used to determine the relation between the causal factors and repeat breeding. The results of this study indicate the prevalence of repeat breeding in Licin Subdistrict, Banyuwangi Regency by 64%. All the factors such as the term of farming, farmer’s ability to detect estrus cycle, and feeding of beef cattle are correlated with the incidence of repeat breeding.